Predicting medical graduates’ clinical performance using national competency examination results in Indonesia - Utomo, Prattama Santoso (BioMed Central Ltd, 2022)
Background: Indonesia has applied a national competency exit-examination for medical graduates since 2014, called The Indonesia Medical Doctor National Competency Examination (IMDNCE). This examination is administered to ensure the competence of medical graduates from at present 83 medical schools in Indonesia. Although many studies reported their evaluation on medical licensing examinations, there are not many studies performed to evaluate the correlation of a national licensing examination to the graduates’ clinical practice. Aims: This research aimed to evaluate the performance of new medical doctors in Indonesia in their internship period after the IMDNCE completion, and whether it might become a predictive indicator for the new medical doctors’ clinical performance. Methods: An observational cross-sectional study was performed in November–December 2017 on 209 doctors who were new medical graduates. Thirty-one senior doctors from a range of regions in Indonesia who were recruited and trained previously participated in the observation. The Clinical Performance Instrument (CPI) tool was developed as an evaluation tool of the new doctors’ clinical competence to be observed for three weeks. The obtained data were analysed using descriptive statistics and correlated to the IMDNCE scores. Results: The mean (95 CI) of the CPI for all participants was 83.0 (80.8–85.2), with no correlation of CPI score with IMDNCE results in domains of communication, professionalism and patient safety (p > 0.05). However, the mean total of the CPI observation scores from doctors who graduated from public medical schools was higher than those graduating from private medical schools. Also, there were differences in scores related to the institution’s accreditation grade (p < 0.05). Conclusion: There is no difference between CPI and national competency examination results. There was no statistical correlation between the clinical performance of new medical doctors during their internship to CBT and OSCE scores in the national competency examination. New doctors’ performance during internship is affected by more complex factors, not only their level of competencies. © 2022, The Author(s).